Terms of endearment: An equilibrium model of sex and matching. Issue 1 (March 2016) - Arcidiacono, Peter; Beauchamp, Andrew; McElroy, Marjorie
Abstract : We develop a two‐sided directed search model of relationship formation that can be used to disentangle male and female preferences over partner characteristics and over relationship terms from only a cross section of observed matches. Individuals direct their search for a partner on the basis of (i) the terms of the relationship, (ii) the partners' characteristics, and (iii) the endogenously determined probability of matching. Using data from the National Longitudinal Study of Adolescent Health, we estimate an equilibrium matching model of high school relationships. Variation in gender ratios is used to uncover male and female preferences. Estimates from the structural model match subjective responses on whether sex would occur in one's ideal relationship. The estimates show that some women would ideally not have sex, but do so out of matching concerns; the reverse is true for men. Counterfactual simulations show that the matching environment black women face is the primary driver of the large differences in sexual activity among white and black women.